Optimalisasi Pemanfaatan E-Commerce dalam Pengembangan Bisnis UMKM - Benardi Benardi; Ranti Karlaili (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2022)
The development of digital technology has brought significant changes in how businesses are conducted, especially in the Micro, Small, and Medium Enterprises (MSMEs) sector. E-commerce has become a key tool for MSMEs to expand their market reach and improve operational efficiency. This seminar discusses the importance of leveraging e-commerce for MSME development in Indonesia, highlighting the potential of digital platforms like social media to enhance market reach and business efficiency. However, challenges such as low digital literacy and inadequate infrastructure remain major barriers to adopting this technology, particularly in rural areas. The seminar results indicate that synergy between the government, private sector, and society is needed to overcome these challenges and support MSMEs in utilizing digital technology for sustainable growth.